A field test of the activity-set hypothesis for warm-up decrement in an open skill - Wrisberg, C. A.; Anshel, M. A. (Research Quarterly for Exercise and Sport, 1993)
Highly skilled tennis players (N = 65) performed 60 forehand and 60 backhand ground strokes, rested for 5 or 15 min, and engaged in one of five interpolated activities: additional rest, running in place, imagery, practice swings, air dribbling). Twelve additional forehands and backhands were performed after those activities. All activities, except additional rest, restored arousal to levels near those of the end of warm-up. Implication: An effective warm-up for applied open skills should include the physical performance of activities that direct the participant's attention to relevant aspects of the task. Activity-specific practices are necessary. They should be maintained between the warm-up and performance, as should physical tasks that maintain the metabolic level of the performer.